Cover Picture: Ab initio Investigation of Interfacial Thermal Transport for HMX‐PVDF Interface (Prop., Explos., Pyrotech. 9/2020). Issue 9 (2nd September 2020) - Fan, Hang; He, Guansong; Yang, Zhijian; Nie, Fude; Chen, Pengwan
Abstract : The cover picture is based on the Full Paper Ab initio Investigation of Interfacial Thermal Transport for HMX‐PVDF Interface by Hang Fan et al., https://doi.org/10.1002/prep.201900418 . The Full Paper can be found on page 1454 ff.